METHOTREXATE AND OSEOPATHY - Feride Göğüş, (Archives of Rheumatology, 2001)
Compared to other immunomodulatory agents methotrexate has less side effects and it is an easy-touse anti-rheumatic drug. That is why it is widely preferred for the treatment of rheumatoid arthritis as well as other inflammatory arthritic conditions. Recently it has been proposed that along with its other side effects, methotrexate can also cause osteopathy. Although there are very few clinical studies on this subject, it is advised to prescribe methotrexate cautiously in elderly patients with severe arthritis and already established severe osteoporosis.